2015
DOI: 10.3389/fped.2015.00019
|View full text |Cite
|
Sign up to set email alerts
|

Atresia of the Aortic Arch in 4-Year-Old Child: A Clinical Case Study

Abstract: Atresia of the aortic arch is a rare congenital heart defect with a high mortality when associated with other intracardiac defects. Cardiac magnetic resonance (CMR) provides the exact anatomy of the aortic arch and collateral circulation and is useful to diagnose-associated aortic arch anomalies. This report describes the case of a 4-year-old child with atresia of the aortic arch, referred to our institution with the diagnosis of aortic coarctation and bicuspid aortic valve. On clinical exam, the femoral pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This fibrous remnant is not visualized on imaging as there is no patent lumen. Nevertheless, the presence of diverticulum on both sides of the distant aortic segments may point towards presence of arch atresia (73).…”
Section: Iaa and Atresia Of Aortic Archmentioning
confidence: 99%
“…This fibrous remnant is not visualized on imaging as there is no patent lumen. Nevertheless, the presence of diverticulum on both sides of the distant aortic segments may point towards presence of arch atresia (73).…”
Section: Iaa and Atresia Of Aortic Archmentioning
confidence: 99%
“…The persistence of fibrous junctions limits the length of the gap between the atretic segments. According to a case reported by Stimato et al, 15 as shown by gadolinium-enhanced magnetic resonance angiography, a patient with aortic atresia had diverticula on both sides of the interrupted zone. This indicates that there were fiber bundles in this area, which is consistent with the diagnostic criteria for AAA.…”
Section: Discussionmentioning
confidence: 96%
“…Although obstructive aortic disease is uncommon, the first-year mortality of aortic interruption or atresia is relatively high if untreated; [1] Hence, the precise identification and comprehensive assessment of the aortic disease are of importance for the timely intervention and the surgical planning, and in particular presentations of obstructive aortic disease vary by the types, locations and degree [2]. One of the phenotypes is ascending aortic hypoplasia, a lesion involving some or all segments of the ascending aorta, which is always combined with other cardiac anomaly, including ventricular septal defect, patent arterial duct or hypoplastic left ventricle.…”
mentioning
confidence: 99%